Working capital management on profitability in consumer product sector / Muhamad Ifwat Mohamed Hanafi - Mohamed Hanafi, Muhamad Ifwat (2018)
Working Capital Management (WCM) is typically determined collectively of the contributing factors of bound firms' profitability. Mainly, the last word goal of any business is to create a profit so the business will continue in operation for an extended run. The management of working capital plays a crucial role in firm gain so as to sustain its growth. Varied findings mentioned that WCM contains a positive relationship with firm gain. However, some papers found a negative relationship between them. Moreover, the chosen tested variables additionally found mixed results by the past researchers, wherever some found a negative relationship between every variable quantity and variable quantity and contrariwise. Thus, these relationships have usually been debated because it has been remarked over time, that working capital management will provides an important impact towards firm profitability. This study was carried out to determine the link between WCM and firm gain from consumer product sector in Malaysia.